Parental Role in Fostering Emotional Intelligence Among Elementary School Students in Puncak Indah Village - Putri, Anzellina; Ramadan, Zaka Hadikusuma (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
Emotional intelligence (EI) is a critical component of development for elementary school children, shaping their ability to identify, regulate, and express emotions appropriately. A strategic aspect of this process is the role of parents as primary educators. This study aims to examine how parents contribute to developing EI in elementary school students in Puncak Indah Village. Using a qualitative case study design, data were collected through in-depth interviews, observations, and documentation, with five families of elementary school children as key informants. The findings reveal that most parents actively serve as role models, mentors, facilitators, and motivators—demonstrating emotional regulation, providing consistent praise and motivation, and applying rational discipline. Despite challenges such as children’s gadget dependence and difficulties in managing social emotions, parents strive to create a supportive emotional environment. The study concludes that active parental involvement significantly enhances children’s EI development, underscoring the family’s role as the foundation for early character education.